Identification predisposition genotypes that contribute to colorectal cancer susceptibility in Malaysia - Ravindran, Ankathil (Pusat Pengajian Sains Perubatan, 2012)
Although this is the first comprehensive study on the association of SNP in xenobiotic metabolizing and DNA damage repair genes in Malaysian population, the study'has been limited by the small sample size due to short ·1 time period and budget. Because of this, large number of samples could not be included. For the same reason, the frequency of variant allele observed for certain SNPs were too small or sometimes nii which must have resulted in inadequate in statistical power. During risk analysis of combination of genotypes, the infrequent presence or rarity of at-risk genotype or allele, for some of the '<Ombination SNPs studied resulted in deriving risk association values with high ORs values, but with extremely wide range of 95% confidence intervals. Such combinations genotypes were not considered as high risk predisposition genotypes despite the high ORs obtained. I Malaysian population comprises 3 maJor ethnic groups; Malay, Chinese and Indian with a ratio of approximately 60:30:10, respectively. Different the ethnic races have different genetic background. The difference in genetic background of the study subjects which comprised these 3 ethnic races was not taken into account and this was another limitation. A stratified analysis based on.ethnicity with equal number of the study subjects in each ethnic group, could have given better results with adequate power. The study subjects in this study were recruited from differing collaborating hospitals in Malaysia. From some of the hospitals, it was difficult and unable to get many of the epidemiological and clinicopathological details of the case subjects. So the interaction of confotinding factors like lifestyle habits (smoking, alcohol consumption), dietary habits etc with the SNP included ~n the study could not be examined.